XUV frequency comb production with an astigmatism-compensated enhancement cavity - Nauta, Janko; Oelmann, Jan-Hendrik; Borodin, A.; Ackermann, A.; Knauer, P.; Muhammad, I; Pappenberger, Ronja; Pfeifer, Thomas; Crespo López-Urrutia, José Ramon (Optics express, 2021)
We have developed an extreme ultraviolet (XUV) frequency comb for performing ultra-high precision spectroscopy on the many XUV transitions found in highly charged ions (HCI). Femtosecond pulses from a 100 MHz phase-stabilized near-infrared frequency comb are amplified and then fed into a femtosecond enhancement cavity (fsEC) inside an ultra-high vacuum chamber. The low-dispersion fsEC coherently superposes several hundred incident pulses and, with a single cylindrical optical element, fully compensates astigmatism at the w0 = 15 µm waist cavity focus. With a gas jet installed there, intensities reaching ∼ 1014 W/cm2 generate coherent high harmonics with a comb spectrum at 100 MHz rate. We couple out of the fsEC harmonics from the 7th up to the 35th (42 eV; 30 nm) to be used in upcoming experiments on HCI frequency metrology.
Gesehen am 23.02.2021